A Pilot Study on Innovative Marketing Strategy and Small Business Survival: Array - Adeola, Adetayo; Oludayo , Ariyo (EuroEconomica, 2021)
This paper, on a pilot scale, examines the effect of innovative marketing strategies on small business survival. Survey research design was adopted and Census sampling technique was used by selecting all SMEs operators without the exception of any, using a sample of 106 registered small businesses in Ijebu- Ode, Ogun State, Nigeria. Ordinary least square regression technique was used and a total of 62 questionnaires were retrieved and considered usable for analysis which represents 59% of the total questionnaire distributed. Results showed that customer focus, market focus and integrated marketing, in that order of potency, have positive and significant effects on survival of small business in Ijebu- Ode, Ogun State, Nigeria. This is in support of innovation theory. The study recommend that small business should emphasis more on the dimensions of innovative marketing strategies in order to achieve and sustain their survival in the marketing environment.